Gambaran Pelaksanaan Prevention Mother to Child Transmission di RSUD Kelas B Dr. R. Sosodoro Djatikoesoemo Kabupaten Bojonegoro - Erliana, Nina; Suryoputro, Antono; Mustofa, Syamsulhuda Budi (Jurnal Promosi Kesehatan Indonesia, 2016)
ABSTRACTEast Java Province in 2014 is the second of a number of provinces in Indonesia which has the prevalence of HIV/AIDS , in Bojonegoro (2015) being the order to -8 from 38 districts/cities in East Java as many as 718 cases of HIV/AIDS , in hospital Class B Dr . R. Sosodoro Djatikoesoemo district of Bojonegoro (2015) there were 178 people in inpatient and outpatient 1126 people with HIV/AIDS cases and 819 pregnant women only 6 were examined HIV in PMTCT services. This research will be conducted to analyze and describe the implementation of the PMTCT program In the Hospital Class B Dr. R. Sosodoro Djatikoesoemo Bojonegoro. This research is a qualitative descriptive exploratory with technique -indepth interviews against 5 key informants (5 Midwifes and 3 Specialist Doctors) and 5 informants triangulation (2 Midwiifes and 3 mothers who follow the PMTCT programs). The results are In the Hospital Class B Dr. R. Sosodoro Djatikoesoemo Bojonegoro haven’t the relevant Director’s SK PMTCT program, but the program is alreadyrun by Director’s SK of Organizational Structure of KPA in Hospital Class B Dr. R. Sosodoro Djatikoesoemo district of Bojonegoro which there PMTCT program implementation team as much as 5 people Midwives (which is already implementing PMTCT training Midwives 3) but never implement PMTCT program socialization to other health personnel at the hospital. PMTCT program is only implemented prongs 3 and 4 only, whereas prongs 1 and 2 has not been implemented because the patients who visit the PMTCT services are integrated in the KIA services only pregnant women, while the given information PMTCT and HIV testing is also only pregnant women who are at risk only , not on any pregnant women who visit. While it has never been no regular schedule related to evaluation and monitoring of the KPA and Bojonegoro District Health Office, but Hospital Class B Dr. R. Sosodoro Djatikoesoemo district of Bojonegoro regularly every month a report on the case of HIV/AIDS.Keywords: HIV/AIDS , pregnant women , PMTCT .